2016
DOI: 10.1007/s10565-016-9340-2
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of hepatoprotective and nephroprotective potential of withaferin A on bromobenzene-induced injury in Swiss albino mice: possible involvement of mitochondrial dysfunction and inflammation

Abstract: Bromobenzene is a well-known environmental toxin which causes liver and kidney damage through CYP450-mediated bio-activation to generate reactive metabolites and, consequently, oxidative stress. The present study aimed to evaluate the possible protective role of withaferin A against bromobenzene-induced liver and kidney damage in mice. Withaferin A (10 mg/kg) was administered orally to the mice for 8 days before intragastric intubation of bromobenzene (10 mmol/kg). As results of this experiment, the levels of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 44 publications
1
17
0
Order By: Relevance
“…The GSH pool is depleted due to the conjugation of epoxides formed by biotransformation of BB, when it is delivered in high doses (Kluwe et al, 1984). Hepatotoxicity induced by BB is characterized by a depletion in glutathione in both mitochondria and cytosol, succeeded by a diminution in mitochondrial respiration at complexes I and II during the start of hepatotoxicity (Vedi and Sabina, 2016). Pre-treatment with beta-carotene significantly increased the reduced glutathione levels brought about by the action of BB in our study.…”
Section: Discussionsupporting
confidence: 53%
“…The GSH pool is depleted due to the conjugation of epoxides formed by biotransformation of BB, when it is delivered in high doses (Kluwe et al, 1984). Hepatotoxicity induced by BB is characterized by a depletion in glutathione in both mitochondria and cytosol, succeeded by a diminution in mitochondrial respiration at complexes I and II during the start of hepatotoxicity (Vedi and Sabina, 2016). Pre-treatment with beta-carotene significantly increased the reduced glutathione levels brought about by the action of BB in our study.…”
Section: Discussionsupporting
confidence: 53%
“…Among these withanolides, withaferin A (WFA) is the most abundant and therapeutically effective withanolides with anti-cancer activities (6)(7)(8). WFA protects against acetaminophen-induced hepatic toxicity (9) and bromobenzene (an environmental toxin)-induced liver and kidney damage (10). Some clinical trials Downloaded from https://academic.oup.com/carcin/article-abstract/40/9/1110/5303994 by Semmelweis University user on 28 November 2019 have investigated the efficacy of W.somnifera extracts (Drug: Sensoril) for bipolar disorder, schizophrenia and generalized anxiety disorder (ClinicalTrials.gov Identifier: NCT00761761, NCT01311180, NCT01793935) and Schlicht and group reported that W.somnifera extracts provided significant benefits in patients with schizophrenia (11).…”
Section: Introductionmentioning
confidence: 99%
“…Mitochondrial dysfunction plays a crucial role in bioenergetics metabolism and non-energetics pathogenesis in many lung diseases [ 6 , 7 ]. The mitochondrial genome acts as a sentinel factor governing the cytotoxic response of lung cells to oxidant stress [ 8 , 9 ]. In this review, we highlight how ROS-induced mitochondrial dysfunction and damaged mitochondrial DNA (mtDNA) fragments are involved in the pathobiology of various degenerative lung diseases, pulmonary fibrosis, and lung tumorigenesis.…”
Section: Introductionmentioning
confidence: 99%